Review of recent advances in post-harvest techniques for tropical cut flowers and future prospects: Heliconia as a case-study - Malakar, Moumita; Paiva, Patrícia Duarte de Oliveira; Beruto, Margherita; Cunha Neto, Antonio Rodrigues da (Frontiers in Plant Science, 2023)
Aesthetic attributes and easy-to-grow nature of tropical cut flowers (TCFs) have contributedto their potential for increased production.The dearth of information regarding agronomic practices and lack of planting materials are the key hindrances against their fast expansion. Unconventional high-temperature storage requirements and the anatomy of the peduncle contribute topoor vase life performance, while troublesome packaging and transport due to unusual size and structureprimarily cause post-harvest quality deterioration. Nonetheless, the exotic floral structuresconsequently increase market demand, particularly in temperate countries. This boosts studies aimed at overcoming post-harvest hindrances. While a few TCFs (Anthurium, Strelitzia, Alpinia, and a few orchids) are under the spotlight, many others remain behind the veil.Heliconia, an emerging specialty TCF (False Bird-of-Paradise, family Heliconiaceae), is one of them. The structural uniquenessand dazzling hues of Heliconia genotypes facilitate shifting its position from the back to the forefrontof the world floriculture trade. The unsatisfactory state-of-the-art of Heliconia research and the absence of any review exclusively on it are the key impetus for structuring this review. In addition to the aforementioned setbacks, impaired water uptake capacity after harvest, high chilling sensitivity, and the proneness of xylem ducts to microbial occlusion may be counted as a few additional factors that hinder its commercialization. This review demonstrates the state-of-the-art of post-harvest research while also conceptualizing the implementation of advanced biotechnological aid to alleviate the challenges, primarily focusing on Heliconia (the model crop here) along with some relevant literature on its other allied members. Standard harvesting indices, grading, and packaging are also part of the entire post-harvest operational chain, but since these phases are barely considered in Heliconia and the majority of tropical ornamentals except a few, a comprehensive account of these aspects has also been given. The hypothesized cues to nip chilling injury, resorting to different bio-chemical treatments, nano-based technology, and advanced packaging techniques, may help overcome preservation difficulties and propel its transition from niche to the commercial flower market. In a nutshell, readers will gain a comprehensive overview of how optimum post-harvest handling practices can rewardingly characterize this unique group of TCFs as the most remunerative component.